PENGEMBANGAN MEDIA PEMBELAJARAN MATEMATIKA POWERPOINT INTERAKTIF BERBASIS REALISTIC MATHEMATIC EDUCATION (RME) DISERTAI GAME DI SMP NEGERI 5 METRO - Icha Mawarinda; Sutrisni Andayani; Yeni Rahmawati (EMTEKA: Jurnal Pendidikan Matematika, 2022)
This study aims to produce interactive powerpoint mathematics learning media based on realistic mathematics education (RME) accompanied by games at SMP Negeri 5 Metro which are declared valid and practical. The research uses the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation), which only focuses on product development, thus the implementation stage is only carried out with a small group sample and the evaluation stage is carried out at each stage. The instruments used are material expert validation sheets, media, language and student response questionnaire sheets. Data analysis techniques used include data analysis validation and product practicality. Based on the results of the study, it was concluded that the interactive powerpoint mathematics learning media based on realistic mathematical education (RME) accompanied by games at SMP Negeri 5 Metro was declared very valid and very practical. The percentage of cavalidity is 92,67%, and the media is stated to be very practical with a percentage of 94%.